A Retrospective Case Series of Pericapsular Nerve Group (PENG) Block for Primary Versus Revision Total Hip Arthroplasty Analgesia - Kukreja, Promil (Cureus, 2020)
The innervation of the hip joint is complex and it is challenging to provide effective analgesia after hip surgery utilizing any single regional anesthesia technique. The pericapsular nerve group (PENG) block is an interfascial plane block aiming to block articular branches supplied by femoral, obturator, and accessory obturator nerves. In this case series, we compare the efficacy of the PENG block to provide analgesia in primary and revision total hip arthroplasty (THA). The ultrasound-guided PENG block technique is described and post-operative pain scores and opioid requirements are reported. The PENG block was successfully used in primary THA as a solo block, and it may be used in combination with other regional blocks for any hip surgery. The PENG block is an easy regional technique to perform in the supine position with motor-sparing benefits.